Respostas
respondido por:
1
Olá, Gabriela.
![\frac{4}{\sqrt7-\sqrt3}+\sqrt3-\sqrt7=\\\\=\frac{4}{\sqrt7-\sqrt3}\cdot\frac{\sqrt7+\sqrt3}{\sqrt7+\sqrt3}+\sqrt3-\sqrt7=\\\\=\frac{4(\sqrt7+\sqrt3)}{7-3}+\sqrt3-\sqrt7=\\\\=\frac{\not4(\sqrt7+\sqrt3)}{\not4}+\sqrt3-\sqrt7=\\\\=\boxed{2\sqrt3} \frac{4}{\sqrt7-\sqrt3}+\sqrt3-\sqrt7=\\\\=\frac{4}{\sqrt7-\sqrt3}\cdot\frac{\sqrt7+\sqrt3}{\sqrt7+\sqrt3}+\sqrt3-\sqrt7=\\\\=\frac{4(\sqrt7+\sqrt3)}{7-3}+\sqrt3-\sqrt7=\\\\=\frac{\not4(\sqrt7+\sqrt3)}{\not4}+\sqrt3-\sqrt7=\\\\=\boxed{2\sqrt3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B%5Csqrt7-%5Csqrt3%7D%2B%5Csqrt3-%5Csqrt7%3D%5C%5C%5C%5C%3D%5Cfrac%7B4%7D%7B%5Csqrt7-%5Csqrt3%7D%5Ccdot%5Cfrac%7B%5Csqrt7%2B%5Csqrt3%7D%7B%5Csqrt7%2B%5Csqrt3%7D%2B%5Csqrt3-%5Csqrt7%3D%5C%5C%5C%5C%3D%5Cfrac%7B4%28%5Csqrt7%2B%5Csqrt3%29%7D%7B7-3%7D%2B%5Csqrt3-%5Csqrt7%3D%5C%5C%5C%5C%3D%5Cfrac%7B%5Cnot4%28%5Csqrt7%2B%5Csqrt3%29%7D%7B%5Cnot4%7D%2B%5Csqrt3-%5Csqrt7%3D%5C%5C%5C%5C%3D%5Cboxed%7B2%5Csqrt3%7D)
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás